Community structure and diversity of benthic macroinvertebrates as bioindicators of water quality in some waterfall ecosystems, Bawean Island, Indonesia - Catur Retnaningdyah; Endang Arisoesilaningsih; Viky Vidayanti; Purnomo Purnomo; Satria Cahya Febriansyah (Society for Indonesian Biodiversity, 2023)
Abstract. Retnaningdyah C, Arisoesilaningsih E, Vidayanti V, Purnomo, Febriansyah SC. 2023. Community structure and diversity of benthic macroinvertebrates as bioindicators of water quality in some waterfall ecosystems, Bawean Island, Indonesia. Biodiversitas 24: 370-378. Bawean Island is a small island with a fairly dense population, so the need for water resources is quite high. On Bawean Island, several waterfalls have been found that have a hydrological function capable of supplying water continuously for drinking water, raw materials, agricultural irrigation functions and other daily activities that are very important for the people of Bawean Island. However, the quality of the waterfall ecosystem on Bawean Island has never been studied. This study aims to evaluate the water quality of some waterfall ecosystems on Bawean Island using the community structure and diversity of benthic macroinvertebrates as a complement to water physicochemical monitoring. This study used the Ex Post Facto method. The research was conducted at 6 waterfalls found on Bawean Island. The physicochemical quality of the water observed included air temperature, water temperature, pH, Dissolved Oxygen (DO), conductivity, Biochemical Oxygen Demand (BOD), nitrate, and Total Phosphate (TP). The quality of the benthic macroinvertebrate that had been monitored included Importance Value Index (IVI), taxa richness, total density, Shannon-Wiener Diversity Index (H’), and an ecological index, namely the Family Biotic Index (FBI). The monitoring data then be used to analyze the interaction between water quality profiles and macroinvertebrates profiles by conducting Principal Component Analysis (PCA). Based on the results obtained, the water quality in the Bawean Island waterfall, according to the FBI index categorized as Good-Excellent. According to Indonesian government regulation (PP. No. 22 of 2021), some parameters of water quality in Putri and Suwari waterfall were classified as class 2, which can be used for water tourism infrastructure, fish farming also agriculture and the others are categorized as class 3 which is only used for fish farming and agriculture. To maintain good water quality, the waterfall manager needs to control human activities around the waterfall’s ecosystem.